Technological globalisation and regional security in East Asia - Boutin, J. D. Kenneth (2009)
Involves a growing disjuncture between processes of techonological development, application and diffusion and individual states, technological globalization contributes distinctively to regional security in East Asia. the potential contribution of technological globalization to sustainable economic development and prosperity are important to regional states due to their contribution to comprehensive security, and has rendered it less threatening in this region than elsewhere. east Asian states have supported the deepening of processes of technological globalization through enacting measures designed to facilitate the integration of local industries into transnational commercial networks on a regional or even global basis.